Surface properties of the ethanol/water mixture: Thickness and composition - Hyde, Anita; Ohshio, M.; Nguyen, C.V.; Yusa, S.I.; Yamada, N.L.; Phan, Chi (ELSEVIER, 2019)
Ethanol is a common amphiphilic solvent often used in conjunction with water. However, despite its widespread use, key questions regarding the thickness and composition of molecules at the ethanol/water/air surface remain unclear. Recent thermodynamic analyses, Bagheri and co-authors (2016) and Santos and Reis (2018), indicated that the interfacial thickness is not constant. However, the interfacial thickness from these two analyses follows opposite trends. This study aims to provide a detailed description of the thickness and composition of the interfacial layer by combining neutron reflectivity (NR) experiments with rigorous molecular simulation. The interfacial composition was determined from molecular simulations and, in conjunction with the Gibbs excess concentration, used to calculate the interfacial thickness. It was found that the thickness decreased exponentially and reached a plateau of ~ 8.2 Å. The results confirm the trends obtained thermodynamically from surface tension. The study also provides a new theoretical framework to describe the interfacial layer of water/alcohol mixtures.